Exploring the impact of chemical composition on aerosol light extinction during winter in a heavily polluted urban area of China. (1st October 2019) - Zhou, Yaqing; Wang, Qiyuan; Zhang, Xu; Wang, Yichen; Liu, Suixin; Wang, Meng; Tian, Jie; Zhu, Chongshu; Huang, Rujin; Zhang, Qian; Zhang, Ting; Zhou, Jiamao; et al.
Abstract: An intensive measurement campaign was conducted in Xi'an, China from December 2012–January 2013 to investigate the chemical composition, formation, and optical properties of PM1 . The PM1 mass concentration (average = 138.8 ± 83.2 μg m −3 ) accounted for ∼50% of the PM2.5 mass. Organic aerosols (OA) and secondary inorganic aerosols (SIA) were the most abundant PM1 components, contributing 53.0% and 35.0% to the mass, respectively. Both primary emissions and aqueous-phase oxidation of secondary aerosols played roles in the pollution episodes. The average light scattering and absorption coefficients during the campaign were 805 ± 581 Mm −1 and 123 ± 96 Mm −1, respectively. Both the mass scattering and mass absorption efficiencies for PM1 were higher than that for PM2.5-1, indicating stronger ability of light extinction for the smaller particles at visible wavelengths compared with the larger ones. The contributions of aerosol species to light extinction coefficients under two visibility conditions were estimated based on multiple linear regression models, and the OA was found to be the largest contributor to light extinction in both cases. A larger contribution of SIA to light extinction for visibility <5 km demonstrated its greater impacts on visibility during heavy pollution conditions. These findings provide insights into the importance of submicron particles for pollution and visibility degradation in northwestern China. Highlights: Organic aerosol and secondary inorganic aerosols were the most abundant PM1 components in Xi'an during winter. Primary emissions and aqueous-phase oxidation were essential in evolution of the pollution episodes. Secondary inorganic aerosols (mainly NH4 NO3 ) play an important role in visibility degradation under severe air pollution.